Intergroup Contact as a Potential Path to Neutralize the Detrimental Effect of National Identification on Xenophobia in Germany - Petia Genkova; Christoph Daniel Schaefer; Simone Karch (Journal of International Migration and Integration, 2021)
Proceeding globalization and the increase in global mobility entail that a growing proportion of people in economically developed countries have a migration background, so that cultural diversity has become an integral characteristic of many societies. Consequently, national identifications and attitudes towards immigrants are gaining importance in both international and intra-societal contexts. Previous studies revealed that in some countries, including Germany, national identification is associated with negative attitudes towards outgroups. In the present article, the interplay between national identification and intergroup contact is analyzed, with xenophobia as the criterion. The study is based on a cross-sectional survey amongst members of the majority population in Germany. It was predicted and found that the association between national identification and xenophobia is moderated by intergroup contact. There was only an association between national identification and xenophobia in participants with below-average or average levels of contact, whilst for those with above-average levels of contact, there was no significant association. Thus, the results point to the importance of contact experiences as a path to neutralize the effects of national identification on xenophobia, possibly by assisting in a redefinition of national belonging.
Keywords: 300; National identification; Xenophobia; Prejudice against immigrants; Contact hypothesis; Neutralizing effect of contact